New chemistry to support the search for more effective opioids - Yang, Ruoyan (2020)
Herein is presented a synthesis route to obtain noroxymorphone, a vital intermediate in the manufacture of opioid medicines, using the major ingredient in opium – morphine as the starting material. Two steps of Albright-Goldman oxidation and the formation of diene are combined in one pot to enhance the efficiency of the whole route. The overall 14% yield is still impractical for industry. However, further optimization of Albright-Goldman oxidation can increase the yield to near 30% in total. Noroxymorphone is employed as a starting material to access new opioid derivatives by N-substitution or conjugate addition of amines onto electron-deficient alkenes.